Assessing parental traits affecting children's food habits: An analysis of the determinants of responsible consumption - Concetta Nazzaro; Marco Lerro; Giuseppe Marotta (Agricultural and Food Economics, 2018)
Over the last decades, economic, social, and environmental changes have profoundly affected citizen-consumer's lifestyle and food habits. Current food habits encourage people either to eat more outside home or to a massive use of convenience foods. The consequence is the increasing rate of overweight and obesity through the population and in particular among children. The resulting social and environmental costs are huge. Indeed, it increases government health expenditure as well as environmental pollution due to the large amount of water, fertilizers, and chemicals involved in the production process. The study focuses on these issues aiming at uncovering the aspects able to encourage healthier and more responsible food habits. Specifically, it explores the effects of different parental characteristics on children's food habits and lifestyle. The study findings reveal a positive effect of parental socio-demographic characteristics (i.e., education and occupation), diet awareness, and lifestyle on children's food habits and lifestyle, offering practical insights for regulators on how to promote healthier and more sustainable food habits among children.
Keywords: 330; Lifestyle; Food habits; Responsible consumption; Overweight; Obesity